Modification of the properties of muscle and vegetable proteins by transglutaminas - Yepishkin, Serhii; Strashynskyi, Igor (My University, 2025)
The results of the studies on the use of microbial transglutaminase in hydrated proteins of animal and plant origin confirm the positive effect on the restructuring of these proteins through the cross-linking reaction. The increase in pH levels occurs due to the formation of ammonia (NH3) as a result of this reaction. According to the obtained experimental data, it is recommended to add 0.05% to 0.1% microbial transglutaminase with an activity of 100-120 units to hydrated protein systems. The prospects for further research lie in the development of a food composition with microbial transglutaminase and hydrocolloids to improve the functional-technological and structural-mechanical properties of meat emulsions and high organoleptic qualities of cooked sausages.
Keywords: кафедра технології м’яса і м’ясних продуктів; hydrated proteins; food proteins; мікробна трансглутаміназа; гідратовані білки; харчові білки